Effectiveness of Family-Centered Auditory and Tactile Sensory Stimulation on Level of Consciousness in Traumatic Brain Injury Patients - Aqidatun Ayu Wulandari; Akhmad Zainur Ridla; Siswoyo Siswoyo; Heri Siswanto (GLOBAL HEALTH SCIENCE GROUP, 2024)
TBI patients with decreased consciousness will experience decreased sensory and stimulus perception as a result of prolonged hospitalization, immobilization, and social isolation. Therefore, sensory stimulation is needed to increase patient awareness. This study aimed to determine the effects of family-centered auditory and tactile sensory stimulation in patients with TBI. A case study was used to describe the intervention in this study. The study sample was an adult patients with TBI admitted to the intensive care unit. The trained family members provided auditory and tactile sensory stimulation once daily for 1 week. Two instruments were used for data collection, the “Glasgow Coma Scale” and the “Fall Outline of Unresponsiveness Score” to assess the patient’s level of consciousness (LOC). The results showed that implementing organized auditory and tactile sensory stimulation by trained family members was increased the average GCS and FOUR score. Patients in this study showed an increase in LOC with a GCS score of 8-14 and FOUR score of 9-14 on 7 days of intervention. Thus, auditory and tactile sensory stimulation by trained family members enhanced the consciousness of patients with trauma-induced brain injury. This method is recommended for patients with traumatic brain injury.